2016
DOI: 10.1128/aac.01794-15
|View full text |Cite
|
Sign up to set email alerts
|

Fumarate-Mediated Persistence of Escherichia coli against Antibiotics

Abstract: g Bacterial persisters are a small fraction of quiescent cells that survive in the presence of lethal concentrations of antibiotics. They can regrow to give rise to a new population that has the same vulnerability to the antibiotics as did the parental population. Although formation of bacterial persisters in the presence of various antibiotics has been documented, the molecular mechanisms by which these persisters tolerate the antibiotics are still controversial. We found that amplification of the fumarate re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 51 publications
1
42
1
Order By: Relevance
“…We propose that Cco-mediated phenazine reduction constitutes a redox-balancing pathway that confers a physiological condition of enhanced ciprofloxacin tolerance (Fig. 4d), in line with previous reports highlighting links between respiration and antibiotic tolerance 27,29,31 . We note that, while the ∆ cco1cco2 mutant shows decreased antibiotic tolerance relative to the WT, it nevertheless shows survival levels that are higher than that of the ∆ phz mutant, indicating that additional mechanisms contribute to the antagonistic effect of phenazines (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…We propose that Cco-mediated phenazine reduction constitutes a redox-balancing pathway that confers a physiological condition of enhanced ciprofloxacin tolerance (Fig. 4d), in line with previous reports highlighting links between respiration and antibiotic tolerance 27,29,31 . We note that, while the ∆ cco1cco2 mutant shows decreased antibiotic tolerance relative to the WT, it nevertheless shows survival levels that are higher than that of the ∆ phz mutant, indicating that additional mechanisms contribute to the antagonistic effect of phenazines (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…We hypothesize that priming respiratory metabolism by the addition of a carbon source and electron acceptor affects both target corruption and other, less-characterized, downstream processes to sensitize cells to quinolones. Remarkably, one study has been able to leverage the metabolic stress induced by extreme levels of intracellular fumarate accumulation to promote a broad range of persistence phenotypes (Kim et al, 2016). This work emphasizes the complex interaction between cellular metabolic activity and drug sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…In E . coli , fumarate accumulation and perturbations of the TCA cycle as well as the electron transport chain has been linked with increased persistence while others have found that inactivation of sucB , encoding α-ketoglutarate dehydrogenase and other genes of the TCA cycle reduced persister formation 15 17 . Tolerance to aminoglycosides is provided by low proton motive force (PMF) as persister cells are eradicated by conditions that enhance PMF and facilitates aminoglycoside uptake 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%